Micro & Macroeconomic determinants of NAV of Islamic equity unit trust funds in Malaysia: qualitative approach - Othman, Anwar Hasan Abdullah (International Academy of Business, International Educators Group, 2012)
This study aims to explore through a qualitative study the factors that influence the net asset value of Islamic equity unit trust funds in Malaysian unit trust industry. A phenomenology method through an in-depth interview was carried out with six informants using the convenience sampling method. After the transcription of the interview data and detailed analysis using the thematic technique, the finding indicated that there are sixteen themes that found have influence on the variance of the net asset value of Islamic equity unit trust fund in Malaysian unit trust industry. These themes categorized into internal and external factors: external factors (Macroeconomics) include economic growth, interest rate, inflation, money supply, foreign exchange rate, crude oil price, local stability, global stability, and regulatory environment. While internal factors (Microeconomics) are fund manager experience, reputation and historical performance, shariah compliant aspect (Islamic law), size of the fund, capital appreciation, income distribution and risk.